Marriage and Ministry: Conflicts and Occupational Conflicts in Wesley’s Life and Ministry - Headley, Tony (The Asbury journal, 2010)
In this article, the author explores John Wesley's perspectives on marriage and how these views related to his practice of ministry. Specifically, the author examines Wesley's developmental journey from believing he could not marry to actually contracting a marriage with Mary Vazeille. Following exploration of Wesley's perspectives on marriage, the author discusses these issues in relation to two observed patterns in his significant intimate relationship with Sophy Hopkey, Grace Murray and Mary Vazeille; namely that for the most part, Wesley cultivated these relationships out of travel and illness. The author concludes that even though Wesley moved from a position of celibacy to contracting a marriage, he never truly resolved the conflict between conjugal and ministry obligations. In fact, Wesley largely operated out of the belief that ministry obligations must always take primacy over marital responsibilities. Finally, the author draws out the implications of this stance for Wesley's ministry and marriage and the lessons current clergy might learn from his example.